Examining the Claims of Natural Resources Rights by the Niger Delta peoples of Nigeria: Array - Amah, Emmanuel Ibiam; Umobong, Moses (Acta Universitatis Danubius. Juridica, 2021)
Under the Nigerian federation, the mineral resources hosting communities of the Niger-delta region of Nigeria have made concerted claims on mineral resources situated in their land territory based on their attachment with their ancestral land. A lot of heated debates have trailed these claims among academics as well as political writers and commentators. While proponents of state ownership, control and management of natural resources rely on the well acceptable principle of state sovereignty, local peoples and communities where natural resources are exploited and their sympathizers based their claim of rights over these resources from the provisions of some international and regional human rights instruments. This work therefore is an attempt to x-ray these varying contentions from the stand point of sovereignty of states and international human rights legal instruments. This paper opined that the exercise of sovereignty by states does not preclude her obligation to accord resource rights to her subnational or indigenous peoples. It calls for legal and policy reforms by the Nigerian government aimed at protecting the rights of indigenous peoples of the Niger Delta region of Nigeria over their natural resources.